ESG Performance and Indonesia Stock Return - Agustin, Isnaini Nuzula; Suhendri, Nindi; Anchao, Wang; Yulfiswandi, Yulfiswandi (Jurnal Riset Akuntansi dan Keuangan, 2024)
As the sustainability become imperative, investors started to pay attention on how ESG performance affect the market performance. This study aims to analyze the influence of ESG performance on stock returns and volatility, with Covid-19 stringency posits as moderating variable. This study include all companies listed on the Indonesia Stock Exchange spans from 2020 to 2022, resulting 150 observations. Employing panel regression, this study exhibit that the Social aspect significantly influence stock returns, while environment aspect has a significant effect on stock return. Further, it has also revealed that covid-19 stringency proved to moderating the relationship between Governance and ESG on stock volatility, implying the prominence of government intervention during the pandemic. This finding is expected to be useful for investors who are concerns on ethical and sustainability point of view. By understanding the ESG- market performance nexus, investors are expected to have clearer picture on sustainable stock selections.